Associations between arterial stiffness, electrolytes, and hormones: insights from the LURIC Study on cardiovascular health - Moissl-Blanke, Angela P.; Delgado Gonzales de Kleber, Graciela; Yücel, Gökhan; Daschner, Clara; Kleber, Marcus E.; Krämer, Bernhard; März, Winfried; Yazdani, Babak (Cardiorenal Medicine, 2025)
Background: Pulse pressure (PP), the difference between systolic (SBP) and diastolic blood pressure (DBP), is an essential marker of cardiovascular (CV) health and arterial stiffness. Elevated PP is linked to a higher risk of CV events, a major cause of global mortality. This study examines its association with key electrolytes—sodium, potassium, calcium, magnesium, phosphate, and vitamin D—in blood pressure regulation and vascular function. - Methods: We analysed data from 3,316 LURIC participants who underwent coronary angiography and had a median follow-up of 9.9 years. Fasting blood samples were collected at baseline. Associations between PP and electrolyte levels were assessed using Spearman correlation. Logistic regression models were used to calculate odds ratios (ORs) per standard deviation (SD) of PP and electrolyte concentrations for four clinical outcomes: all-cause mortality, CV mortality, reduced eGFR, and type 2 diabetes mellitus. - Results: The cohort’s average age was 62.7 years, with 70% of participants being male. Higher PP was significantly associated with older age, increased BMI, and the prevalence of coronary artery disease (CAD), carotid stenosis (CS), and peripheral arterial disease (PAD). Potassium, phosphate, renin, 25-OH, and 1,25-OH vitamin D concentrations decreased significantly as PP increased, while sodium remained unchanged. Sodium-potassium ratio and aldosterone-renin ratio increased with higher PP. Women had a higher risk of CV mortality per SD of PP (OR 1.57; 95% CI 1.33-1.86), while men showed a greater risk of reduced eGFR (OR 1.59; 95% CI 1.40-1.80). - Conclusion: Specific electrolyte imbalances are closely linked to increased PP and arterial stiffness. Our findings highlight sex-specific CV risk and support further research into nutrient-based and hormonal interventions targeting PP modulation.
Auf der Verlagsfrontdoor des Artikels ist der Name Yücel fälschlich mit einem q am Ende geschrieben
Gesehen am 17.11.2025